Contemporary American fiction - Brauner, David, 1968- (Edinburgh critical guides to literature., 2010)
This is an accessible, lucid and incisive study that will prove indispensable to students and scholars of contemporary American fiction. Featuring a wide range of authors - from canonical figures such as Philip Roth, Don DeLillo and Annie Proulx, to increasingly influential writers such as Jeffrey Eugenides, Gish Jen and Richard Powers - the book combines detailed readings of key texts with informative discussions of their historical, social and cultural contexts. There are chapters focusing on formal characteristics (the use of irony and paradox in novels by Don DeLillo, Paul Auster and Bret Easton Ellis, and the generic properties of the texts and films of Cold Mountain, Brokeback Mountain and No Country for Old Men) and on thematic concerns (the representation of gender and sexuality in novels by Jane Smiley, Carol Shields and Jeffrey Eugenides, and of ethnicity, race and hybridity in fiction by Gish Jen, Philip Roth and Richard Powers). Running through all these chapters is an interrogation of all three elements making up the phrase 'contemporary American fiction'. Key Features Identifies some of the main trends in contemporary American fiction and situates them in historical and cultural contexts Discusses a representative range of recent fiction, providing a sense of the rich diversity of the field and of its key themes and modes of writing Introduces students to a variety of critical approaches to, and debates concerning, contemporary American fiction Encourages reflection on the nature of national, gender, ethnic and generic identities